In-stent restenosis is associated with proliferative skin healing and specific immune and endothelial cell profiles: results from the RACHEL trial - Lozano, Íñigo; Bangueses, Roi; Rodríguez, Isabel; Pevida, Marta; Rodríguez-Aguilar, Raúl; Rodríguez, Diana; Espasandín-Arias, Martina; Llames, Sara; Meana, Álvaro; Suárez, Ana; Rodríguez-Carrio, Javier (Frontiers in Immunology, 2023)
Introduction: in-stent restenosis (ISR) is a major challenge in interventional cardiology. Both ISR and excessive skin healing are aberrant hyperplasic responses, which may be functionally related. However, the cellular component underlying ISR remains unclear, especially regarding vascular homeostasis. Recent evidence suggest that novel immune cell populations may be involved in vascular repair and damage, but their role in ISR has not been explored. The aims of this study is to analyze (i) the association between ISR and skin healing outcomes, and (ii) the alterations in vascular homeostasis mediators in ISR in univariate and integrative analyses. Methods: 30 patients with ≥1 previous stent implantation with restenosis and 30 patients with ≥1 stent without restenosis both confirmed in a second angiogram were recruited. Cellular mediators were quantified in peripheral blood by flow cytometry. Skin healing outcomes were analyzed after two consecutive biopsies. Results: hypertrophic skin healing was more frequent in ISR patients (36.7%) compared to those ISR-free (16.7%). Patients with ISR were more likely to develop hypertrophic skin healing patterns (OR 4.334 [95% CI 1.044–18.073], p=0.033), even after correcting for confounders. ISR was associated with decreased circulating angiogenic T-cells (p=0.005) and endothelial progenitor cells (p<0.001), whereas CD4+CD28null and detached endothelial cells counts were higher (p<0.0001 and p=0.006, respectively) compared to their ISR-free counterparts. No differences in the frequency of monocyte subsets were found, although Angiotensin-Converting Enzyme expression was increased (non-classical: p<0.001; and intermediate: p<0.0001) in ISR. Despite no differences were noted in Low-Density Granulocytes, a relative increase in the CD16- compartment was observed in ISR (p=0.004). An unsupervised cluster analysis revealed the presence of three profiles with different clinical severity, unrelated to stent types or traditional risk factors. Conclusions: ISR is linked to excessive skin healing and profound alterations in cellular populations related to vascular repair and endothelial damage. Distinct cellular profiles can be distinguished within ISR, suggesting that different alterations may uncover different ISR clinical phenotypes.